Endodontic Procedural Errors: Frequency, Type of Error, and the Most Frequently Treated Tooth. (10th August 2015) - Yousuf, Waqas; Khan, Moiz; Mehdi, Hasan
Abstract : Introduction. The aim of this study is to determine the most common endodontically treated tooth and the most common error produced during treatment and to note the association of particular errors with particular teeth. Material and Methods. Periapical radiographs were taken of all the included teeth and were stored and assessed using DIGORA Optime. Teeth in each group were evaluated for presence or absence of procedural errors (i.e., overfill, underfill, ledge formation, perforations, apical transportation, and/or instrument separation) and the most frequent tooth to undergo endodontic treatment was also noted. Results. A total of 1748 root canal treated teeth were assessed, out of which 574 (32.8%) contained a procedural error. Out of these 397 (22.7%) were overfilled, 155 (8.9%) were underfilled, 16 (0.9%) had instrument separation, and 7 (0.4%) had apical transportation. The most frequently treated tooth was right permanent mandibular first molar (11.3%). The least commonly treated teeth were the permanent mandibular third molars (0.1%). Conclusion. Practitioners should show greater care to maintain accuracy of the working length throughout the procedure, as errors in length accounted for the vast majority of errors and special care should be taken when working on molars.